The seascape nursery: a novel spatial approach to identify and manage nurseries for coastal marine fauna. Issue 2 (2nd October 2013) - Nagelkerken, Ivan; Sheaves, Marcus; Baker, Ronald; Connolly, Rod M
Abstract: Coastal marine and estuarine ecosystems are highly productive and serve a nursery function for important fisheries species. They also suffer some of the highest rates of degradation from human impacts of any ecosystems. Identifying and valuing nursery habitats is a critical part of their conservation, but current assessment practices typically take a static approach by considering habitats as individual and homogeneous entities. Here, we review current definitions of nursery habitat and propose a novel approach for assigning nursery areas for mobile fauna that incorporates critical ecological habitat linkages. We introduce the term 'seascape nurseries', which conceptualizes a nursery as a spatially explicit seascape consisting of multiple mosaics of habitat patches that are functionally connected. Hotspots of animal abundances/productivity identify the core area of a habitat mosaic, which is spatially constrained by the home ranges of its occupants. Migration pathways connecting such hotspots at larger spatial and temporal scales, through ontogenetic habitat shifts or inshore–offshore migrations, should be identified and incorporated. The proposed approach provides a realistic step forward in the identification and management of critical coastal areas, especially in situations where large habitat units or entire water bodies cannot be protected as a whole due to socio‐economic, practical or other considerations.